Gestão estratégica na cafeicultura: eficiência de fatores produtivos e quantificação de emissões de gases do efeito estufa - Oliveira, Diego Humberto de (2015)
With the macroeconomic restorations in the late 20th century the coffee market sector organized itself in a new arrangement. Premises of management different from the traditional were institutionalized on the coffee market, and the demands of consumers about the sustainability then began being oriented to industries, so that being they could offer products that were different from the rest began demanding them from coffee growers. Thus being, the lack of management preparation inherited down from past regulations interferes in economic results of production, and many coffee growers don’t even search for a differential in terms of their own product. Moreover, during the productive cycles the quantity of production factors are effected without the technical recommendations, which may economically render the production or have a direct impact on the environment. With the new demands of consumption, which remits sustainable production, in some moment in time the situation could lead to the loss of commercial opportunities. The product, therefore, demands information to act strategically on your own business. The main objective for this project is suggest a process for the strategic management of coffee producing, considering the economic and environmental aspects. We analyzed the economic viability of a fertilizer formulated NPK when applied in different levels of irrigated coffee areas and quantify their gas emissions that cause the greenhouse gases (GHG). The analyses contemplated the harvests of 2012/2013 and 2013/2014 of an experiment conducted at the Federal University of Lavras (UFLA). The outlining was made in random blocks with six treatments and four repetitions, being six levels of fertilization with fertilizers containing N, P2O5 e K2O that were from 10, 40 ,70 ,100 ,130 and 160% of recommended standards for coffee producers of dry farming. The emissions of GHG were based on the in indices from the IPCC to nitrous oxide (N2O) and carbon dioxide (CO2). There was a significant effect from the levels of fertilizers in effect in relation with the productivity on the biennium, and the maximum production was reached with the application of the fertilizer on the level of 145,57% of the recommended standard. The optimal economic production occurred with the application on the level of 118,12%. The economic maximum and optimal productions on the biennium generated a gross margin of R$ 18.205,73/ha and R$ 19.127,81/ha respectively, considering only the costs of fertilizers that was the variable factor. When the emissions of GHG which maximized the production generated 7,42 tons of carbon equivalent (tCO2e) per hectare, while the optimal economic quantity generated 6,02 tCO2e/ha; a difference of 18,86%.